Evidence of early defects in Cajal–Retzius cell localization during brain development in a mouse model of dystroglycanopathy. (24th March 2017) - Booler, H. S.; Pagalday‐Vergara, V.; Williams, J. L.; Hopkinson, M.; Brown, S. C.
Abstract : Aims: The secondary dystroglycanopathies represent a heterogeneous group of congenital muscular dystrophies characterized by the defective glycosylation of alpha dystroglycan. These disorders are associated with mutations in at least 17 genes, including Fukutin‐related protein ( FKRP ). At the severe end of the clinical spectrum there is substantial brain involvement, and cobblestone lissencephaly is highly suggestive of these disorders. The precise pathogenesis of this phenotype has, however, remained unclear with most attention focused on the disruption to the radial glial scaffold. Here, we set out to investigate whether lesions are apparent prior to the differentiation of the radial glia. Methods: A detailed investigation of the structural brain defects from embryonic day 10.5 (E10.5) up until the time of birth (P0) was undertaken in the Fkrp‐deficient mice (FKRP KD ). Reelin, and downstream PI3K/Akt signalling pathways were analysed using Western blot. Results: We show that early basement membrane defects and neuroglial ectopia precede radial glial cell differentiation. Furthermore, we identify mislocalization of Cajal–Retzius cells which nonetheless is not associated with any apparent disruption to the reelin, and downstream PI3K/Akt signalling pathways. Conclusions: These observations identify Cajal–Retzius cell mislocalization as an early event during the development of cortical defects thereby identifying an earlier onset and more complex pathogenesis than originally reported for the secondary dystroglycanopathies. Overall this study provides new insight into central nervous system involvement in this group of diseases. Abstract : Brain involvement in severe phenotypes of dystroglycanopathies includes abnormal cortical neuronal migration leading to type II, or cobblestone, lissencephaly. In embryonic Fkrp‐deficient mice (FKRP KD ) basement membrane abnormalities and mislocalisation of Cajal‐Retzius cells are early events in the development of cortical defects.